2014
DOI: 10.1111/cfs.12143
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of theON FIREpeer support programme for children and adolescents in families with mental health problems

Abstract: A B S T R AC TChildren in families with mental health problems may encounter multiple risks to their well-being. General aims of peer support programmes for these children include fostering resilience and effective coping strategies, and enhancing self-esteem and social skills. This study aimed to evaluate outcomes from a pilot multi-site implementation of the ON FIRE peer support programme. The purpose of ON FIRE is to cultivate hope, resilience and well-being in children and adolescents aged 8-17 years livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 31 publications
1
45
0
Order By: Relevance
“…This study was part of a larger study investigating the impact and outcomes of the ON FIRE program (see Foster, McPhee, Fethney, & McCloughen, 2014). The present study employed an exploratory qualitative design.…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of a larger study investigating the impact and outcomes of the ON FIRE program (see Foster, McPhee, Fethney, & McCloughen, 2014). The present study employed an exploratory qualitative design.…”
Section: Methodsmentioning
confidence: 99%
“…Outcomes of peer support programmes have been positively evaluated (Foster, McPhee, Fethney, & McCloughen, 2014), and the experiences of peer support for young people identified (Foster, Lewis, & McCloughen, 2014). Engaging school students is also supported through mental health promotion strategies (http://www.kidsmatter.edu.au).…”
Section: New South Walesmentioning
confidence: 99%
“…One common intervention offered to these young people are peer support programs, which aim to connect young people with other youth in similar life circumstances (Foster et al 2014b). A recent randomised controlled trial (RCT) of a peer support group delivered to youth in the Netherlands found significant post intervention decreases in participants' negative thoughts and emotional and behavioural difficulties (van Santvoort et al 2014).…”
Section: Introductionmentioning
confidence: 99%